ANALISIS IMPLEMENTASI PROGRAM SEKOLAH SEHAT DALAM MEMBENTUK KARAKTER PEDULI LINGKUNGAN - Natasya Della Indriyani; Wawan Syahiril Anwar; Mira Mirawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Natasya Della Indriyani 037121135. Analysis of the Implementation of the Healthy School Program in Shaping Environmental Awareness Character.This study aims to determine how the implementation of the Healthy School Program contributes to shaping the environmental awareness character of fourth-grade students at SD Negeri Polisi 1 Kota Bogor. This research uses a qualitative method with a Descriptive Study Approach. Data collection techniques include observation, interviews, and documentation. The results show that the implementation of the Healthy School Program in shaping students' environmental awareness character has been carried out quite well, through various activities such as promoting clean and healthy living behavior (PHBS), proper sanitation, greening, and fostering environmentally friendly habits. In addition, teachers play an active role as role models in establishing positive habits, supported by adequate school facilities. Although there are still some challenges, such as a lack of understanding of waste management and limited facilities, overall the program is effective in shaping students’ character and environmentally conscious habits